Analysis of critical thinking ability of class X senior high school students - Cacik, Sri; Widiyanti, Ifa Seftia Rakhma (Univeritas Papua, 2024)
Students' critical thinking abilities influence the development of cognitive, affective and psychomotor abilities. Students who have critical thinking ability are able to analyze a problem so they can make decisions. The aim of the research is to determine and describe the initial critical thinking abilities of class X students at MA Nurul Huda, Central Java. This research is quantitative research based on critical thinking ability tests. The instrument used is a test sheet in the form of multiple-choice questions which contains indicators of critical thinking abilities. The results of the research are critical thinking abilities which are categorized into five, namely very good, good, sufficient, low, and very low. Based on data analysis, it is known that the initial critical thinking ability of grade X MA Nurul Huda Central Java students for very good, good, sufficient, low, and very low categories is 0%, 4,54%, 31,82%, 50%, and 13,64%. Therefore, it can be concluded that the critical thinking ability of class X students at MA Nurul Huda, Central Java, is low and needs to be improved.